Difficulties of learning pronunciation for EFL students (Journal of Pedagogical Inventions and Practices, 2024)
Learning pronunciation can be a challenging aspect of acquiring a new language, especially for English as a Foreign Language (EFL) students. The difficulties can stem from various factors such as differences in phonetic systems, lack of exposure to native speakers, and the influence of the students' first language on their pronunciation. This abstract explores the common challenges faced by EFL students when learning pronunciation and suggests strategies to help them improve their skills in this area